Fabrication of the X-Ray Mask using the Silicon Dry Etching - Hiroshi TSUJII; Kazuma SHIMADA; Makoto TANAKA; Wataru YASHIRO; Daiji NODA; Tadashi HATTORI (Journal of Advanced Mechanical Design, Systems, and Manufacturing, 2008)
The X-ray lithography of uses synchrotron radiation is one of the microprocessing structure fabrication technology. In X-ray lithography, precision of the fabricated structure is influenced by precision of the X-ray mask considerably. Conventionally, the X-ray mask was fabricated with UV lithography. However, it is difficult to fabricate the highly precise X-ray mask because of the tapering X-ray absorber. We introduces the ability of Si dry etching technology into UV lithography in order to fabricate untapered, high precision X-ray masks containing rectangular patterns. This new X-ray mask fabrication method uses a high-precision microstructure pattern formed by Si dry etching, thereby fabricating high aspect ratio, narrow line width resist microstructures that cannot be achieved by any conventional technology. An Au for the X-ray absorber is made to the groove of the structure, and it is formed by electroplating. The silicon substrate itself is used as seed layer and the structure is fabricated with the photo resist whose resistance is higher than silicon. It can be expected the gilding growth from only the bottom layer. High-density Au functions sufficiently as an absorber. Au plating was formed only from the base of the structure ditch and could bury Au of thickness 3.5μm in a narrow place of 2.7μm in width well. The fabricated structure using X-ray lithography. Highly-precise rectangular structure could be fabricated.